Production of tumor necrosis factor alpha in human leukocytes stimulated by Cryptococcus neoformans. - Levitz, S M (1994)
Tumor necrosis factor alpha (TNF-alpha) is a key mediator of inflammation and may promote human immunodeficiency virus replication in latently infected cells. Since cryptococcosis often is associated with aberrations in the host inflammatory response and occurs preferentially in persons with AIDS, we defined the conditions under which human leukocytes produce TNF-alpha when stimulated by Cryptococcus neoformans. Peripheral blood mononuclear cells (PBMC) produced comparable amounts of TNF-alpha following stimulation with C. neoformans and lipopolysaccharide. Detectable TNF-alpha release in response to C. neoformans occurred only when fungi with small-sized capsules were used and complement-sufficient serum was added. Fractionation of PBMC established that monocytes were the predominant source of TNF-alpha. TNF-alpha gene expression and release occurred significantly later in PBMC stimulated with C. neoformans than in PBMC stimulated with LPS. C. neoformans was also a potent inducer of TNF-alpha from freshly isolated bronchoalveolar macrophages (BAM). Upon in vitro culture, BAM and monocytes bound greater numbers of fungal cells, yet their capacity to produce TNF-alpha following cryptococcal stimulation declined by 74 to 100%. However, this decline was reversed if the BAM and monocytes were cultured with gamma interferon. These data establish that C. neoformans can potently stimulate TNF-alpha release from human leukocytes. However, several variables profoundly affected the amount of TNF-alpha released, including the type of leukocyte and its state of activation, the size of the cryptococcal capsule, and the availability of opsonins.